AN IN –VITRO COMPARATIVE STUDY OF WETTABLITY OF TWO COMMERCIALLY AVAILABLE SALIVA SUBSTITUTES AND DISTILLED WATER ON HEAT – POLYMERISED ACRYLIC RESIN - DR NAGAM RAJAREDDY; DR HIMABINDU G; DR RAVI KUMAR P; DR CHAVVA SRUTHI; DR BVS KRISHNAKANTH; DR YOSHITHA B (The Bioscan, 2026)
Background: Denture retention remains as complex issue influenced by multiple physical factors. Adequate retention is essential for successful complete dentures, relying on mechanisms such as adhesion, cohesion, surface tension, and wettability. Wettability, defined as the ability of a liquid to spread over a solid surface, plays a key role in enhancing denture retention. Improved wetting reduces interfacial energy and strengthens adhesion between saliva and the denture base. Aim: To compare the wettability of two commercially available saliva substitutes and distilled water on heat-polymerized acrylic resin. Materials and Methods: 120 heat-cured acrylic resin samples of 2 mm thickness were prepared. Tissue surfaces were left unpolished, while the opposite surfaces were finished and cleaned. Samples were divided into three groups: wet mouth, distilled water and E-saliva. Contact angles were measured using a goniometer and analyzed statistically. Results: Results showed that E-saliva exhibited the lowest contact angle, indicating superior wettability, followed by wet mouth and distilled water. Thus, E-saliva demonstrated the best potential for improving denture retention. Conclusion: Within the limitations of the present study the following conclusion can be drawn. Among the three groups the advancing and receding contact angles for group the group 3 (E saliva) is lesser than group 1(wet mouth) which is less than group 2(distilled water). Therefore the wettability of E saliva is greater than wet mouth which is greater than distilled water.